12*x+48=51*x-117

Simple and best practice solution for 12*x+48=51*x-117 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12*x+48=51*x-117 equation:


Simplifying
12x + 48 = 51x + -117

Reorder the terms:
48 + 12x = 51x + -117

Reorder the terms:
48 + 12x = -117 + 51x

Solving
48 + 12x = -117 + 51x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-51x' to each side of the equation.
48 + 12x + -51x = -117 + 51x + -51x

Combine like terms: 12x + -51x = -39x
48 + -39x = -117 + 51x + -51x

Combine like terms: 51x + -51x = 0
48 + -39x = -117 + 0
48 + -39x = -117

Add '-48' to each side of the equation.
48 + -48 + -39x = -117 + -48

Combine like terms: 48 + -48 = 0
0 + -39x = -117 + -48
-39x = -117 + -48

Combine like terms: -117 + -48 = -165
-39x = -165

Divide each side by '-39'.
x = 4.230769231

Simplifying
x = 4.230769231

See similar equations:

| X=16a+1 | | 77077= | | 2y=y+11 | | (2x-4)/x=2 | | Ln(x^2-1)=1 | | X+.09x=11 | | 3(2-3x)-4=-(4x-5)+2 | | 62x+110=668 | | 62x+110=168 | | 5/6/1/7 | | Y-3=0(x-4) | | 2x+3=4(2+1) | | content://media/external/file/31459 | | 3x+7=12x+6 | | 9x-11=x+10 | | 16+9x-1-5x=-15+10x | | 16+9x-1-5x=15+10x | | 8a-4(-5a-7)=14a | | x=m | | 33-5v=2v+5 | | (a-10)+(a+10)=0a | | 14/15=x/105 | | 03651= | | 7.5=n-2.6 | | 7.5=nz | | X+1.6=0.6 | | ax+4=5+b | | (2m+3)x^2+(4m-2)x-(m+1)=0 | | (2m-3)x^2+(4m-2)x-(m+1)=0 | | 120x-2x^2=1800 | | 13-m=59 | | Y/17=4 |

Equations solver categories